2010
DOI: 10.1016/j.jmmm.2010.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic detection of sigma phase in duplex stainless steel UNS S31803

Abstract: a b s t r a c tDuplex stainless steels are high strength and corrosion resistant steels extensively used in the chemical and petrochemical industry. The best mechanical properties and corrosion resistance are obtained with a microstructure composed by equal parts of ferrite and austenite and free from tertiary phases. Sigma phase is one of these deleterious tertiary phases. In the present work different amounts of sigma phase were precipitated by heat treatments in a UNS S31803 stainless steel. Some specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 15 publications
1
38
0
18
Order By: Relevance
“…Conforme o esperado, as micrografias mostram que na medida em que se aumenta o tempo de tratamento térmico, aumenta-se consideravelmente a concentração de precipitados de sigma na superfície de material, estando em concordância com as referências [2,12].…”
Section: Avaliação Da Técnica De Voltametria Linear Para Determinaçãounclassified
See 2 more Smart Citations
“…Conforme o esperado, as micrografias mostram que na medida em que se aumenta o tempo de tratamento térmico, aumenta-se consideravelmente a concentração de precipitados de sigma na superfície de material, estando em concordância com as referências [2,12].…”
Section: Avaliação Da Técnica De Voltametria Linear Para Determinaçãounclassified
“…Desta forma, estudos apontam para a necessidade da criação de um Ensaio Não Destrutivo (END) que possa ser utilizado para quantificar, preferencialmente em campo, a presença de fase sigma em aços duplex [10][11][12][13][14][15].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The correspondence between the microstructure and the magnetic response of stainless steels, including its variation during phase transformations, was the object of a series of studies by Tavares and co-workers [31][32][33] . Their work was done using measurements of saturation magnetization, remanence, coercive force and magnetic transition temperature, and included the magnetic response as a function of ferrite/austenite proportion 31 , high and low temperature embrittlement 32 and specific measurements aimed at sigma phase formation 33 .…”
Section: Barkhausen Noise Measurementsmentioning
confidence: 99%
“…Their work was done using measurements of saturation magnetization, remanence, coercive force and magnetic transition temperature, and included the magnetic response as a function of ferrite/austenite proportion 31 , high and low temperature embrittlement 32 and specific measurements aimed at sigma phase formation 33 . In the latter case, the Ferritscope and Magnetic saturation Use measurements were used, and the authors observed that both methods are sensitive to small fractions of sigma.…”
Section: Barkhausen Noise Measurementsmentioning
confidence: 99%